2004
DOI: 10.1136/bjo.2003.018523
|View full text |Cite
|
Sign up to set email alerts
|

Removal of sodium from the solvent reduces retinal pigment epithelium toxicity caused by indocyanine green: implications for macular hole surgery

Abstract: Backgrounds/aims: Staining of internal limiting membrane with indocyanine green (ICG) has been reported to be associated with postoperative atrophic retinal pigment epithelium (RPE) change. Here the authors examined whether removing sodium from the solvent reduces ICG induced RPE cytotoxicity. Methods: Human RPE cells were exposed to ICG (0.25 and 0.025 mg/ml) reconstituted with balanced salt solution (BSS) or Na + free BSS. Light microscopy, trypan blue dye exclusion, acridine orange/ethidium bromide staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 22 publications
1
24
0
2
Order By: Relevance
“…sodium iodate, has been proposed to gain access to the RPE cell layer by two mechanisms: flow through the idiopathic MH or crossing through all retinal layers. Several investigations in vivo in various animal models have suggested ICG to be hazardous to the RPE in a dose-dependent manner [50,51,52,53]. Recently, Czajka et al [52] simulated human MH surgery to test the effects of ICG on the retina in a novel porcine model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sodium iodate, has been proposed to gain access to the RPE cell layer by two mechanisms: flow through the idiopathic MH or crossing through all retinal layers. Several investigations in vivo in various animal models have suggested ICG to be hazardous to the RPE in a dose-dependent manner [50,51,52,53]. Recently, Czajka et al [52] simulated human MH surgery to test the effects of ICG on the retina in a novel porcine model.…”
Section: Discussionmentioning
confidence: 99%
“…Sippy et al [53] reported that a short exposure of in vitro cultured human RPE cells to 0.1% ICG solution resulted in decreased mitochondrial enzyme activity, but did not influence the cellular morphology itself. Recently, Ho et al[ 50, 51] have postulated that removal of Na + from the solvent reduces ICG-induced RPE toxicity. Further in vivo studies are necessary to confirm the exact mechanism by which ICG induces RPE damage.…”
Section: Discussionmentioning
confidence: 99%
“…Direct toxicity, upregulation of apoptosis-related genes, 19 hypoosmolarity of the solvent, 20 intraoperative retinal illumination, 21,22 and the role of sodium were hypothesized as possible factors that could increase retinal ICG toxicity. 23,24 There are several limitations in our study. Fluorogold has been used for decades as the standard dye for retrograde labeling of RGCs.…”
Section: Discussionmentioning
confidence: 94%
“…Several investigations in various animal models have suggested that ICG may be hazardous to the RPE [87,100,101,102,103,104,105]. Experiments in rats by Enaida et al [84] showed that moderate to high doses (2.5 or 25 mg/ml) of intravitreal ICG were toxic to retinochoroidal cells, and impaired retinal function was described even at low doses of ICG (0.025 mg/ml).…”
Section: Complicationsmentioning
confidence: 99%
“…(1) The dye should be diluted in nonsaline solution to avoid precipitation and to decrease the risk of Na-dependent toxicity [101]. …”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%